Estudo do desempenho mecânico de compósitos de cimento-microcelulose - Mancuzo, Veronica Liss Carvalho (2019)
Composite materials are increasingly studied in the most diverse fields of technology, presenting properties capable of, along with their matrix, improve their performance and deliver an innovative and high-performance product. The goal of this research is to study the mechanical performance of cementitious composites reinforced with microcrystalline cellulose, or M.C.C. In order to carry out tensile tests in flexion and axial compression, specimens with concentrations of 1.5%, 3% and 4.5% of MCC were framed based on the cementitious matrix, being the dispersion of the particles carried out through ultrasonic bath. Also, porosimetry tests were performed to correlate with the increase or decrease of the resistance. After the mechanical tests, a 26% increase on the compressive strength was noticed, which could not be observed regarding flexural tensile strength, which showed no significant difference between the standard and MCC reinforced samples. The results could be closely associated to the current type of sand, since in pilot tests, values of resistance to both compression and flexion were significantly higher than in the present study.